Validation of Rubia urceolata X.F.Wang & C.H.Wang (Rubiaceae) from Central China - He, Hai (Phytotaxa, 2018)
In a recent issue of Phytotaxa, Wang et al. (2018) described a new species of Rubia Linnaeus (1753: 109) from western Hubei, Central China and proposed the name as “R. urceolata X.F.Wang & C.H.Wang” based on the gathering WCHH17061 (WH) as its holotype. However, in a separate paragraph subtitled “Additional specimens examined (paratypes)”, other three gatherings (WCHH17064, LZHE17082 and WCHH17113, all deposited in WH), which collected at different localities and/or on separate dates from WCHH1761, were cited by mistake also as “holotype”. This practice made “R. urceolata X.F.Wang & C.H.Wang” invalid since more than one gathering was designated as holotype (here Art. 8.2 Note 1 does not apply and it is against Art. 40.7; Turland et al. 2018).